A Developmental Perspective on The Impact on Children of Both Witnessing and Experiencing Domestic Violence: A Narrative Literature Review - Pugh, Eleanor J.; Cengotitabengoa, Mónica Martínez-; Nichols, Ayla Freij-; Martinez, Daniel Long-; Cengotitabengoa, Maria-Teresa Martínez - (International Journal of Psychosocial Rehabilitation, 2024)
This narrative literature review presents recent research investigating the developmental outcomes in children of experiencing and witnessing domestic violence in childhood. The structure of this review organises child outcomes of domestic violence identified for each developmental stage of a child’s growth, beginning with impact in utero and extending to adolescence and adulthood. Inclusion and exclusion criteria were closely followed to maintain rigorous synthesis of research published within the last 20 years, thus providing an extensive insight into domestic violence impacts on child development. Critical analysis of the current body of literature concluded that further research is required to consider a more holistic approach to understanding the effects of domestic violence, which recognises the simultaneous presence of alternative harmful factors to the child, such as parental substance misuse, as well as extending experiences of domestic violence to those of males.